RELEVANSI PENDIDIKAN ISLAM DALAM MEMBINA AKHLAK UMAT DI TENGAH PERUBAHAN SOSIAL - Arif Fikri; Auliansyah Raja; Al Adam; Ardian Al Hidaya; Nabila Rispa Izzaty; Nurainun Lubis (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2026)
Education plays a strategic role in shaping character and fostering the morals of Muslims as the moral foundation of both individuals and society. Education focuses not only on intellectual development but also emphasizes the internalization of religious values ​​that can shape good and responsible behavior. This study aims to analyze the role of education as a means of moral development, the challenges faced, and effective methods in its implementation. The research method used is a qualitative literature study approach, through the collection and analysis of literature from books, journals, and academic documents related to Islamic education and morals. The results show that education can be a means of moral development through the introduction of social and religious norms from an early age, the role model of educators, the habituation of positive behavior, and the synergy between formal, non-formal, and informal education. In addition, challenges to moral education include the influence of modernity, the digital era, misinformation, limitations of educators, and differences in societal understanding. Therefore, an effective moral development strategy must be adaptive to current developments, but still based on noble religious and moral values. By implementing appropriate educational methods, it is hoped that the younger generation will be able to internalize noble morals, develop a character of integrity, and form a harmonious, morally upright society that adheres to Islamic teachings.